The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s00787-021-01839-x
|View full text |Cite
|
Sign up to set email alerts
|

What treatment outcomes matter most? A Q-study of outcome priority profiles among youth with lived experience of depression

Abstract: Interest in youth perspectives on what constitutes an important outcome in the treatment of depression has been growing, but limited attention has been given to heterogeneity in outcome priorities, and minority viewpoints. These are important to consider for person-centred outcome tracking in clinical practice, or when conducting clinical trials targeting specific populations. This study used Q-methodology to identify outcome priority profiles among youth with lived experience of service use for depression. A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…In a previous Q-study involving a sample of youth with lived experience of depression, we identified four outcome priority profiles. Youth, respectively, focused on “ relieving distress and experiencing a happier emotional state ”; “ learning to cope with cyclical distressing emotional states ”; “ understanding and processing distressing emotional states ”; and “ reduced interference of ongoing distressing emotional states with daily life ” [ 40 ]. The first youth profile conveyed a similar focus on symptom reduction and enhanced well-being as the practitioner super profile A super .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous Q-study involving a sample of youth with lived experience of depression, we identified four outcome priority profiles. Youth, respectively, focused on “ relieving distress and experiencing a happier emotional state ”; “ learning to cope with cyclical distressing emotional states ”; “ understanding and processing distressing emotional states ”; and “ reduced interference of ongoing distressing emotional states with daily life ” [ 40 ]. The first youth profile conveyed a similar focus on symptom reduction and enhanced well-being as the practitioner super profile A super .…”
Section: Discussionmentioning
confidence: 99%
“…The Q-set used in the present study was developed through a multi-stage process involving stakeholder workshops, a systematic review of youth depression treatment studies [ 28 ]; and a qualitative analysis of youth and clinicians’ outcome narratives following treatment for depression [ 31 ]. A detailed description of this process has been published elsewhere [ 40 ]. The final Q-set consisted of 35 cards, each of which carried an outcome description.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to answering our research questions, we propose further reflections regarding the two cases and its implications. We know from previous research in the field of personal recovery that we need to take the clients’ subjective account into consideration when establishing the outcome of treatments [ 56 ]. Although both patients reported reduced depressive symptoms at follow-up, Sonja’s subjective experience one year after treatment was that nothing had improved or that she might even be feeling worse.…”
Section: Discussionmentioning
confidence: 99%
“…Q methodology research with children and adolescents has appeared in many disciplines including childhood and youth studies ( Kerpelman et al, 2002 ; Metzger et al, 2016 ), psychology ( Richards et al, 2007 ; Krause et al, 2021 ), and primary education ( Tan et al, 2015 ). To our knowledge there have not been any Q studies conducted with children or adolescents regarding their reading experience, despite the method’s increasing acceptance in both compulsory education research ( Lundberg et al, 2020 ) and audience research ( Davis and Michelle, 2011 ).…”
Section: Methodsmentioning
confidence: 99%